2018
DOI: 10.5194/acp-18-10593-2018
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol–cloud interactions in mixed-phase convective clouds – Part 2: Meteorological ensemble

Abstract: Abstract. The relative contribution of variations in meteorological and aerosol initial and boundary conditions to the variability in modelled cloud properties is investigated with a high-resolution ensemble (30 members). In the investigated case, moderately deep convection develops along sea-breeze convergence zones over the southwestern peninsula of the UK. A detailed analysis of the mechanism of aerosol–cloud interactions in this case has been presented in the first part of this study (Miltenberger et al., … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 59 publications
3
12
0
Order By: Relevance
“…Miltenberger et al (2018a) found substantially larger cloud cells in simulations of summertime deep convective clouds with higher aerosol concentrations compared to a low aerosol environment. In addition, these aerosol-induced changes were statistically significant compared to the uncertainty introduced by a meteorological ensemble (Miltenberger et al, 2018b). However, their aerosol concentrations are much larger than observed for the Arctic environment and in deep convective clouds latent heating from condensation and turbulence are stronger than in shallow stratocumulus.…”
Section: Discussionmentioning
confidence: 85%
“…Miltenberger et al (2018a) found substantially larger cloud cells in simulations of summertime deep convective clouds with higher aerosol concentrations compared to a low aerosol environment. In addition, these aerosol-induced changes were statistically significant compared to the uncertainty introduced by a meteorological ensemble (Miltenberger et al, 2018b). However, their aerosol concentrations are much larger than observed for the Arctic environment and in deep convective clouds latent heating from condensation and turbulence are stronger than in shallow stratocumulus.…”
Section: Discussionmentioning
confidence: 85%
“…An important finding is the fact that a heterogeneous CCN distribution with a mean concentration corresponding to that of the reference run (continental assumption), can yield to precipitation deviations ranging in the same order of magnitude than changing the total CCN concentration. The fact that soil moisture and aerosol perturbations contribute in a similar magnitude to the precipitation totals suggests that aerosols are indeed important for quantitative precipitation forecast (Miltenberger et al, 2018). The smallest deviations from the reference runs occurred when introducing orography uncertainties.…”
Section: Discussionmentioning
confidence: 93%
“…Due to a low vertical resolution in the ECMWF ensemble, low‐level variations (e.g., low‐level wind shear) among the ensemble members may not be captured representatively. Considerable uncertainty remains in our understanding and modeling of deep convective clouds and their nonlinear interactions with different processes, because model grid scales are typically several orders of magnitude larger than the process scales (Miltenberger et al, ). Real atmospheric conditions are much more complicated than the idealized conditions proposed here, particularly in environments favorable for deep convection.…”
Section: Resultsmentioning
confidence: 99%
“…Although the importance of intrinsic predictability limits has been acknowledged in weather forecasting, its implications for the evaluation of cloud microphysics parameterizations has been less well addressed (Miltenberger et al, 2018). The uncertainty was also determined for the six hydrometeor species employed in the microphysics scheme, so that we could determine for which species the results were most uncertain under the different perturbations.…”
Section: 1029/2018jd029899mentioning
confidence: 99%
See 1 more Smart Citation